2019
DOI: 10.1371/journal.pone.0221577
|View full text |Cite
|
Sign up to set email alerts
|

Practice pattern of aerosol therapy among patients undergoing mechanical ventilation in mainland China: A web-based survey involving 447 hospitals

Abstract: Background and objective Aerosol therapies are widely used for mechanically ventilated patients. However, the practice pattern of aerosol therapy in mainland China remains unknown. This study aimed to determine the current practice of aerosol therapy in mainland China. Methods A web-based survey was conducted by the China Union of Respiratory Care (CURC) from August 2018 to January 2019. The survey was disseminated via Email or WeChat to members of CURC. A questionnaire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…Nebulization of mucoactive agents is thought to reduce accumulation of thick and sticky airway secretions [ 4 ]. Mucoactive agents are often used in combination with bronchodilators to enhance mobilization of mucus by opening the airways [ 5 , 6 , 7 ]. Manual hyperinflation [ 8 , 9 , 10 ] or mechanical in–exsufflation (MI–E), (commonly referred to as cough assist) [ 8 , 11 , 12 ], may be helpful techniques in mobilizing airway secretions from smaller to larger airways, where it can be removed using suctioning.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nebulization of mucoactive agents is thought to reduce accumulation of thick and sticky airway secretions [ 4 ]. Mucoactive agents are often used in combination with bronchodilators to enhance mobilization of mucus by opening the airways [ 5 , 6 , 7 ]. Manual hyperinflation [ 8 , 9 , 10 ] or mechanical in–exsufflation (MI–E), (commonly referred to as cough assist) [ 8 , 11 , 12 ], may be helpful techniques in mobilizing airway secretions from smaller to larger airways, where it can be removed using suctioning.…”
Section: Introductionmentioning
confidence: 99%
“…Nebulization of mucoactive agents is thought to reduce accumulation of thick and sticky airway secretions [4]. Mucoactive agents are often used in combination with bronchodilators to enhance mobilization of mucus by opening the airways [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, such care is unequally distributed across different levels of hospitals. Tertiary hospitals are the best equipped and provide advanced medical investigation and treatment to referrals from primary and secondary hospitals (Zhang et al, 2019 ).…”
Section: Methodsmentioning
confidence: 99%
“…While as much as 30% of aerosols are typically inhaled, a greater proportion of administered aerosols will be exhausted, leading to concerns regarding secondhand exposure of healthcare providers and families to medical aerosols (67). However, surveys reported that the usage rate of protective filters on the expiratory limb of ventilator circuits was only 24-40% (68,69).…”
Section: Impact Of Exhaled Aerosols and Fugitive Emission During Mechanical Ventilationmentioning
confidence: 99%
“…Most patients (82%) received bronchodilators, followed by corticosteroids (13%), anti-infectious drugs (5%, primarily colistin), and mucolytics (3%, primarily acetylcysteine), and 38% of patients received >2 medications. Another recent survey conducted in China revealed bronchodilators (64.8%) were the most administered drugs, followed by mucolytic agents (44.2%), corticosteroids (43.4%), and antibiotics (16.5%), using USNs (48.3%), JNs (39.2%), VMNs (14.6%), and pMDIs (15.4%) (69). The discrepancies between these two studies could be attributed to physician training, drug/device availability, and insurance system coverage.…”
Section: Discrepancies In Practice Related To Aerosol Delivery Through Mechanical Ventilationmentioning
confidence: 99%